A comprehensive review of ultra-wideband antennas for 5G applications. (27th October 2022) - Mahmud, Md. Zulfiker; Jiddney, Md. Ashik; Rahman, Mahbubur; Samsuzzaman, M.; Althuwayb, Ayman A.; Islam, Mohammad Tariqul
Globally, wireless communication technology is expanding quickly due to the increasing number of wireless devices. About 20 billion devices were connected to the internet at the end of 2020. As current 1G, 2G, 3G, and 4G LTE technologies have their limitations; researchers have been prompted to seek alternative solutions that can connect billions of devices with higher facilities like smart cities, virtual reality, e-healthcare, and different types of real-time communications. This paper presents an extensive review of concepts and techniques of ultra-wideband (UWB) antennas for fifth-generation (5G) communications and their recent uses in wireless communications leading to higher performance. Fifth-generation antennas are capable of connecting 1 million devices per square kilometre, transmitting high speed data up to 2 GBps, and with a latency less than 10 ms. The goal of this article is to provide microwave researchers with in-depth information on 5G antenna technologies and recent developments.